Coincidence: The Grounding Problem, Object-Specifying Principles, and Some Consequences. (1st September 2016) - Sidelle, Alan
Abstract: This paper lays out the basic structure of any view involving coincident entities, in the light of the grounding problem. While the account is not novel, I highlight fundamental features, to which attention is not usually properly drawn. With this in place, I argue for a number of further claims: (1) The basic differences between coincident objects are modal differences, and any other differences between them need to be explained in terms of these differences. More specifically, the basic difference is not a difference in sort. (2) A number of recent defenses of coincidence, which share the basic structure I outline, misidentify what, in their accounts, plays the basic role of addressing (if not solving) the grounding problem. More tentatively, I argue (3) Coincident entities differ only in these modal properties, and properties they entail. In particular, they do not differ in properties like 'being a tree, ' 'being a statue, ' or aesthetic properties, and finally (4) in light of how the account of coincidence offered addresses the grounding problem, the grounding problem provides no reason to prefer monism to pluralism.